Analisis Data Pengujian Mesin Scotch-Brite untuk Menghaluskan Permukaan Cat pada Kabinet Piano - Susanto, Herry -; Didik , Didik; Erwin; Siregar, Rolan; Esye, Yendi; Dwiki , Dwiki (Fakultas Teknik Universitas Darma Persada, 2025)
The piano manufacturing industry comprises multiple stages to achieve a high-quality product, one of which is the surface finishing of the cabinet after sealer coating. In many woodworking industries, this finishing process is still performed manually using scotch-brite, which requires significant labor and extended processing time. To enhance efficiency, the design and performance evaluation of a scotch-brite machine, manually operated by an operator, were conducted. The objective of this study is to assess the machine’s performance and compare its efficiency with conventional manual finishing. Experimental tests were carried out using ten board samples coated with basecoat or sealer. Each sample was subjected to ten sanding cycles at inverter frequency variations of 30 Hz, 35 Hz, 40 Hz, 45 Hz, and 50 Hz. The initial gloss level of the samples was 18 GU, while the finishing standard ranged between 10–14 GU. The optimal result was obtained at 50 Hz, producing an average gloss of 12.4 GU. The sanding process for ten samples required 223 seconds, equivalent to 3.7 minutes. The scotch-brite machine demonstrated higher efficiency, achieving an efficiency level of 53.5%, reducing processing time by approximately 4.2 minutes compared to the manual method, and lowering operator workload. These findings indicate that the machine can effectively support improved quality, consistency, and productivity in the piano manufacturing industry.